Constructing bioinspired hierarchical structure in polymer based energetic composites with superior thermal conductivity. (1st April 2019) - He, Guansong; Li, Xin; Dai, Yu; Yang, Zhijian; Zeng, Chengcheng; Lin, Congmei; He, Songwei
Abstract: Inspired by the microlayered and highly oriented structure of naturally nacre, we reported a thermally conductive polymer based energetic composite constructed with an alternating microlayered structure, in which the one-dimensional (1D) CNTs filled layer acted as bridge to link the adjacent two-dimensional (2D) graphene filled layer. This ordered arrangement of microlayers was similar to the hierarchical 'brick-and-mortar' structure of nacre. As a result, the thermal conductivity ( K ) of composites with an artificial nacre-like structure was obviously higher than those with other structure designs, such as filled by pure graphene/CNTs, or hybrid graphene/CNTs. Moreover, the K enhancing effect could become more pronounced with the layer number due to the synergetic effect of microlayered structure. In addition, the nonlinear dependence of K on the layer number was well fitted by an analytical model which incorporated the synergetic effect. The thermal conduction mechanism could change from series thermal structure to parallel thermal structure with the layer number increasing. Finally, the calculated results of thermal shock resistance and thermal stress distribution confirmed that the enhanced thermal environment adaptability by the construction of alternating microlayered micro/nano-scale structure. This thought based on bioinspired engineering provides a creative opportunity for design and fabrication of novel thermally conductive materials.